Association between ergonomic risk exposures and insomnia symptoms: a mediation analysis of the 5th Korean working conditions survey - Seong-Sik Cho; Tae-Won Jang; Mo-Yeol Kang (BMC Public Health, 2024)
Abstract Background This study investigates the relationship between ergonomic risk exposures and insomnia symptoms, using data representative of Korea’s general working population. Methods Data from the 5th Korean Working Conditions Survey were used for this study. The eligible population (employees) for the current study was 37,026. Insomnia symptoms were estimated using the minimal insomnia symptom scale (MISS) questionnaire. Logistic regression analysis was conducted to explore the association between ergonomic risks and insomnia symptoms. Results All the investigated ergonomic risks increased odd ratios (ORs) for insomnia symptoms: Tiring or painful positions (OR, 1.64; 95% CI, 1.43–1.88); lifting or moving heavy loads (OR, 2.33; 95% CI, 1.99–2.71); long periods of standing (OR, 1.47; 95% CI, 1.29–1.69); and repetitive hand or arm movements (OR, 1.46; 95% CI, 1.29–1.67). The mediated proportion of musculoskeletal pain was 7.4% (95% CI, 5.81–10.13), and the mediated proportion of feeling of exhaustion was 17.5% (95% CI, 5.81–10.13). Conclusions This study provides evidence for the relationship between ergonomic risks and insomnia symptoms, for which musculoskeletal pains and the feeling of exhaustion may be potential mediators.